The effect of grain surface on the long afterglow properties of Sr2MgSi2O7: Eu2+, Dy3+. (April 2016) - Hai, Ou; Jiang, Hongyi; Xu, Dong; Li, Ming
Graphical abstract: The afterglow curves of phosphors sintered again in reducing atmosphere (dash line) compared with that sintered one time (solid line) obtained by different pulverizing ways. Highlights: The luminescence properties of Sr2 MgSi2 O7 : Eu 2+, Dy 3+ phosphors with different grain surface morphology were researched. We found that different pulverizing methods show significantly different impact on the luminescence properties of phosphors. Roller milling should be adopted when the application of luminous powder was at room temperature. Ball milling is an appropriate pulverizing way when the application of luminous powder was in reducing atmosphere at high temperature. The grain surface has a great effect on luminescence performance. Abstract: Sr2 MgSi2 O7 : Eu 2+, Dy 3+ was chosen for the investigation about the effect of grain surface on the long afterglow properties. Three pulverizing ways (manual grinding, ball milling and roller milling) were carried out to obtain different grain surface morphologies of particles. The most grains of the luminous powders obtained by roller milling are intact, while those obtained by ball milling are tattered with the grains surface destroyed. As for manual grinding, part of the grains surface are destroyed. The initial luminescent intensity of the phosphor pulverized by roller milling is nearly twice of that prepared by ball milling. After ball milling, the pulverized phosphor is sintered once again at 1000 °C in reducing atmosphere. It follows that the luminescence properties are enhanced significantly with the opposite variation trend compared with that prepared by roller milling. This is closely related to the change of defect density on the grain surface of these phosphors.